Intersectionality, identity work and migrant progression from low‐paid work: A critical realist approach. Issue 6 (3rd March 2020) - Netto, Gina; Noon, Mike; Hudson, Maria; Kamenou‐Aigbekaen, Nicolina; Sosenko, Filip
Abstract : This article contributes to developing intersectionality theory by deepening understanding of how patriarchy and racism interact with other structural factors to influence low‐paid migrants' progression attempts. Using a critical realist approach and analysing interviews of 31 female and male migrants employed in five large organizations in Scotland and England, we reveal how major structural factors influence their main forms of identity work and the resources that they draw on in both the workplace and home. The feminist approach undertaken by this study makes significant advances to organizational intersectional theory in three ways. Firstly, it highlights the importance of examining the interaction of the influence of patriarchy within the home with racism and other structuring forces within the workplace. Secondly, it reveals how combinations of constraints and enablements that intersect with gendered and racialized identity work create formidable barriers to progression. Thirdly, it explores migrants' differential access to diverse resources, including financial, social, discursive and psychological resources in both spheres over time. These findings reinforce the need for policy actions that recognize the interaction of structural factors which influence female and male migrant progression and the need for support within and beyond the workplace.